2020
DOI: 10.1016/j.psychres.2020.113100
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 scale: Psychometric characteristics, reliability and validity in the Israeli population

Abstract: Mental health clinicians worldwide have been expressing concerns regarding the broad psychological effects of the COVID-19 pandemic. Nonetheless, only a few studies have thus far evaluated the degree of fear of COVID-19, partially due to the lack of validated measures. In this study we evaluated the psychometric properties of the Hebrew version of the Fear of COVID-19 scale (FCV-19S), recently developed to assess different aspects of the fear of the pandemic, in a normative population of participants in Israel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

84
357
6
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 449 publications
(462 citation statements)
references
References 27 publications
(30 reference statements)
84
357
6
15
Order By: Relevance
“…Our study replicated common reports that the FCV-19S provides a unidimensional assessment of fear of COVID-19 (Ahorsu et al, 2020;Alyami et al 2020;Perz et al 2020;Sakib et al 2020;Satici et al 2020;Soraci et al 2020;Tsipropoulou et al 2020). The only exception is a study reporting on results from a Hebrew version (Bitan et al 2020) where the authors proposed that items 1, 2, 4, and 5 (generally afraid, uncomfortable thinking about COVID-19, afraid of losing life, anxious from news) form a factor called emotional fear reactions and that item 3, 6, and 7 (clammy hands, lack of sleep, heart racing) be grouped into a factor called symptomatic expressions of fear. Pakpour et al (2020) argued that the statistical approach used by Bitan et al (2020) was inappropriate and that a con rmatory factor analysis should have been used instead of a principal components analysis where a two-factor was forced even though a single-factor solution had already indicated that a t was adequate.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our study replicated common reports that the FCV-19S provides a unidimensional assessment of fear of COVID-19 (Ahorsu et al, 2020;Alyami et al 2020;Perz et al 2020;Sakib et al 2020;Satici et al 2020;Soraci et al 2020;Tsipropoulou et al 2020). The only exception is a study reporting on results from a Hebrew version (Bitan et al 2020) where the authors proposed that items 1, 2, 4, and 5 (generally afraid, uncomfortable thinking about COVID-19, afraid of losing life, anxious from news) form a factor called emotional fear reactions and that item 3, 6, and 7 (clammy hands, lack of sleep, heart racing) be grouped into a factor called symptomatic expressions of fear. Pakpour et al (2020) argued that the statistical approach used by Bitan et al (2020) was inappropriate and that a con rmatory factor analysis should have been used instead of a principal components analysis where a two-factor was forced even though a single-factor solution had already indicated that a t was adequate.…”
Section: Discussionsupporting
confidence: 87%
“…None of the items were mis tting and were well within the acceptable range of -2.50 to 2.50. Due to a previous report of a two-factor structure of the scale (Bitan et al 2020), the results were inspected for any indications of multidimensionality in the present dataset. The residual correlation coe cients for items 3, 6, and 7…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as fear of uncertainty and negative consequences is also known to be a key variable in effective health communication (Finset et al 2020), Ahorsu et al (2020) recently developed the Fear of . This scale has already been translated from its original Persian version to other languages such as Arabic (Alyami et al 2020), Bangla (Sakib et al 2020), English (Harper et al 2020), Hebrew (Bitan et al 2020), and Turkish (Satici et al 2020), but studies are now needed to explore the function of fear of COVID-19 in relation to pandemic-related health behaviors. Studies using samples from New Zealand and the UK have reported that fear of COVID-19 could be a motivator for engaging in relevant health behaviors and adhering to lockdown rules (Harper et al 2020;Winter et al 2020).…”
Section: Introductionmentioning
confidence: 99%